PROFIL MOTIVASI BERPRESTASI PESERTA DIDIK SMP NEGERI 2 KARANGPAWITAN GARUT - Imas Winwin Yunia; Euis Eti Rohaeti; Devy Sekar Ayu Ningrum (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2020)
The purpose of this study is to know the idea of the achievement motivation of educated person VII grade at SMP Negeri 2 Karangpawitan Garut. Achievement motivation is influenced by intrinsic factors and extrinsic factors. Intrinsic factors are factors that come from within the individual, such as  curiosity, challenge and effort. But extrinsic factors are those that come from outside the individual, such a reward and punishment. Intrinsic and extrinsic motivations play a crucial role in encouraging individuals to achieve. The approach in this research is a quantitative approach with a quantitative descriptive research type. The research sample was 54 students of grade VII. Methods of data collection using a scale of achievement motivation. Based on the research results, it is known that the achievement motivation of class VII students is generally in the moderate achievement motivation category. However, the achievement motivation profile based on gender found that the achievement motivation of female students was better than the achievement motivation of male students. Keywords: Achievement Motivation, Students.